PENGEMBANGAN INOVASI PEMBELAJARAN EKONOMI MIKRO DENGAN MODEL ADDIE - FORIJATI, Rr.; ANAS, M.; ROSIDHAH, ENY (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
The purpose of this study is to develop learning innovations in Microeconomics courses with the ADDIE model. The steps in this learning are 1) analysis, design, development, implementation and evaluation. Microeconomic learning innovation is a learning tool consisting of: Lesson description, brief lesson plans, essential questions, learning concepts, standard learning content, learning objectives, time required, materials and teaching aids, preparation, implementation of learning. The method used in this research is the ADDIE model development method with 6 validators consisting of 2 learning design validators, 2 scientific validators and 2 learning technologies validators. Data were analyzed using descriptive qualitative and quantitative analysis. The results of the learning design expert test assessed that the microeconomic learning innovation on qualifications was good, the results of the scientific field test showed that the microeconomic learning innovation on the qualifications was very good. The results of the learning model test on good qualifications. Qualitatively it can be concluded that microeconomic learning innovations can be used for the teaching and learning process. From the results of the field test the use of microeconomic learning innovations shows good qualifications.